2014
DOI: 10.1371/journal.pone.0092132
|View full text |Cite
|
Sign up to set email alerts
|

Lifespan Psychomotor Behaviour Profiles of Multigenerational Prenatal Stress and Artificial Food Dye Effects in Rats

Abstract: The consumption of artificial food dye (AFD) during childhood and adolescence has been linked to behavioural changes, such as hyperactivity. It is possible that the vulnerability to AFDs is modified by prenatal stress. Common consequences of prenatal stress include hyperactivity, thus potentially leading to synergistic actions with AFDs. Here, we investigated the compounding effect of multigenerational prenatal stress (MPS) and AFD consumption on the development of hyperactivity and anxiety-related behaviours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…Female rats were isolated starting at the age of 90 days until parturition, thus withdrawing the benefit of social interaction and generating both physiological and behavioural changes. The stress severity was comparable, yet different in nature, to an established semi-random restraint and swim stress procedure used in earlier transgenerational studies629. TPS and MPS both reduced total hippocampal GR density, which resembles changes commonly seen after prenatal stress43031.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Female rats were isolated starting at the age of 90 days until parturition, thus withdrawing the benefit of social interaction and generating both physiological and behavioural changes. The stress severity was comparable, yet different in nature, to an established semi-random restraint and swim stress procedure used in earlier transgenerational studies629. TPS and MPS both reduced total hippocampal GR density, which resembles changes commonly seen after prenatal stress43031.…”
Section: Discussionmentioning
confidence: 77%
“…Prenatal programming of the developing brain and HPA axis has consequences that extend into adulthood, which may result in altered motor activity24642. The present study examined animals at the age of 30, 60 and 90 days, thus covering the main stages of adolescent development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous work showed that http multi-generational experience of recurrent PNS accumulates across generations and sensorimotor impairments in later generations exceed the effects of PNS in the first generation (Erikson et al, 2014;Yao et al, 2014). Contrary to such sensorimotor deficits, we propose that some essential cognitive functions may reveal adaptive changes of stress coping in multi-generational prenatal stressed (MGPNS) rats.…”
Section: Introductionmentioning
confidence: 84%